PENGARUH MEDIA PENDINGIN MINYAK PELUMAS SAE 40 PADA PROSES QUENCHING DAN TEMPERING TERHADAP KETANGGUHAN BAJA KARBON RENDAH - Bahtiar, Bahtiar; Iqbal, Muh.; Supramono, Supramono (Jurnal MEKANIKAL, 2014)
Abtstract: The Effect of Lubricating Oil SAE 40 As Cooling Media of Quencing and Tempering Processes on Strenghth of Low Carbon Steel. This study was conducted to determine the effect of lubricating oil SAE 40 as cooling media of quenching and tempering process on the mechanical properties of low carbon steel. Quenching process is done for 7 min, 1 and 2 hours holding times at 925 ℃. Furthermore, tempering process consumes 14 minutes, 1 and and 2 hours holding times at 450 ℃. The raw material for the steel specimen is ST 42. Charpy impact test using a method based on ASTM standards E23-02. The results of impact testing the highest impact toughness values obtained for the heat treatment process then diquencing is 2033 KJ / m 2, at 925oC with a heating holding time 7 minutes, the lowest value is 523 KJ / m 2. The results of testing the highest impact toughness values obtained for the heat treatment process then diquencing and given treatment at a temperature of 450 ℃ tempering at 2607 KJ / m 2, at 925oC with a heating holding time 7 minutes and tempering holding time of 14 minutes, the lowest value is 776 KJ / m 2 , at 925oC with a heating holding time 2 hours minutes and tempering holding time is 2 hours. Keywords: queccing, tempering, cooling media, lucricating oil & strenghth